Reshaping Stage Art: How the Illusory Engine Leads the Innovative Transformation of Stage Design - Li, Bing; Wang, Yu; Zheng, Wei (Transactions on Economics, Business and Management Research, 2023)
This study mainly explores the role of the illusory engine in leading the innovative transformation of stage design, and how this innovative transformation affects stage art. As a powerful three-dimensional visualization engine, illusory engine has achieved great success in video games, film production and other fields. However, in recent years, the application of illusory engine in stage design has gradually attracted attention. This paper will analyze the innovative application cases of illusory engine in stage design and explore its reshaping effect on stage art. The illusory engine in contemporary stage art has a significant impact on stage design and promotes the innovation and transformation of stage art.